2016
DOI: 10.3748/wjg.v22.i44.9744
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2/angiopoietin-1 as non-invasive biomarker of cirrhosis in chronic hepatitis C

Abstract: AIMTo evaluate the efficacy of peripheral blood concentrations of angiopoietins (Ang) as cirrhosis biomarkers of chronic hepatitis C (CHC).METHODSAng1 and Ang2 serum levels were measured by enzyme-linked immunosorbent assays (ELISA) in samples from 179 cirrhotic and non-cirrhotic CHC patients, classified according to the METAVIR system. Groups were compared by non-parametric Mann-Whitney U test. Subsequently, the association of peripheral concentrations of angiopoietins with the stage of fibrosis was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…[ 27 ] The concentration of Ang1 was significantly lower in the serum of cirrhotic patients compared the concentration in the non-cirrhotic ones, and Ang2 serum levels were higher in patients with cirrhosis. [ 28 ] Zhao et al [ 29 ] demonstrated that Ang2 activated the AT1R/PI3K/Akt pathway, which further activated NF-κB, consequently leading to an increased expression of matrix metalloproteinase (MMP)-2 and MMP-9 and migration in breast cancer cells. In consistent with our findings, activated NF-κB pathway was attributed to HFLS acceleration, thus facilitating the progress of RA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] The concentration of Ang1 was significantly lower in the serum of cirrhotic patients compared the concentration in the non-cirrhotic ones, and Ang2 serum levels were higher in patients with cirrhosis. [ 28 ] Zhao et al [ 29 ] demonstrated that Ang2 activated the AT1R/PI3K/Akt pathway, which further activated NF-κB, consequently leading to an increased expression of matrix metalloproteinase (MMP)-2 and MMP-9 and migration in breast cancer cells. In consistent with our findings, activated NF-κB pathway was attributed to HFLS acceleration, thus facilitating the progress of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, a retrospective study by Hernández-Bartolomé et al . [29] analyzing 179 patients had previously demonstrated that although Ang-1 was decreased in cirrhotic compared with non-cirrhotic patients, Ang-2 was significantly increased as the stage of liver disease progressed. Moreover, these authors demonstrated that the ratio of serum Ang-2 to Ang-1 displayed notable accuracy (82.1%) for the diagnosis of cirrhosis at the optimal cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HCV-associated cirrhosis and HCC, several angiogenesis soluble factors were significantly upregulated in the blood plasma, including TIMP-1, TIMP-2, HGF, angiopoietin 1, angiopoietin 2, VEGFA, IP-10, PDGF, KGF and FGF. AUROC analysis highlighted especially the potential of angiopoietin 2, a growth factor that belongs to the angiopoietin/Tie signaling pathway [ 119 , 120 , 121 ]. Additionally, CCL20, a secreted chemokine detected in HCCs, promotes blood vessel formation during chronic HCV infection [ 122 ].…”
Section: Signaling Pathways Associated With Candidate Serum Biomarmentioning
confidence: 99%